2005
DOI: 10.1681/asn.2005060584
|View full text |Cite
|
Sign up to set email alerts
|

Microalbuminuria and Coronary Heart Disease Risk in an Ethnically Diverse UK Population

Abstract: Microalbuminuria (MA) is a strong risk factor for subsequent chronic disease, both renal and coronary heart disease (CHD), in European origin populations, but CHD risks differ by ethnicity, and it was hypothesized that prevalence of MA and relations with CHD may also differ. Combined analyses of two population-based cohorts started in 1988 and consisted of 1460 Europeans (70% male), 946 South Asians (78% male), and 559 African Caribbeans (51% male) who resided in London and were aged 40 to 69. Baseline fasting… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
28
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(31 citation statements)
references
References 37 publications
3
28
0
Order By: Relevance
“…According to the multivariate analysis, white individuals seem to exhibit lower proteinuria than other ethnicities at any given GFR, irrespective of the underlying type of disease. Consistent with results of interracial studies in healthy adults and children (8,9), this observation points to potential genetic differences between ethnic groups in the regulation of renal protein handling. Such genetic disposition may contribute, independent of environmental factors, to the faster CKD progression and higher incidence of ESRD in nonwhite populations.…”
supporting
confidence: 84%
“…According to the multivariate analysis, white individuals seem to exhibit lower proteinuria than other ethnicities at any given GFR, irrespective of the underlying type of disease. Consistent with results of interracial studies in healthy adults and children (8,9), this observation points to potential genetic differences between ethnic groups in the regulation of renal protein handling. Such genetic disposition may contribute, independent of environmental factors, to the faster CKD progression and higher incidence of ESRD in nonwhite populations.…”
supporting
confidence: 84%
“…An association between albuminuria and atherosclerotic diseases has been reported in a number of previous papers; albuminuria is known to be a predictor of cardiovascular mortality, although its capabilities may differ according to gender, race, and ethnicities (15,16), and albuminuria is an independent predictor for carotid intima-media thickness in diabetic (17) as well as non-diabetic (18) subjects. There have also been several studies that have assessed the possible association of low eGFR with carotid atherosclerosis in individuals who had only a mild decline in renal function, and in the general population.…”
Section: Discussionmentioning
confidence: 85%
“…Based on a population-based survey in the United Kingdom of nearly 3000 subjects, Tillin et al documented differences in the prevalence of microalbuminuria among differing racial/ethnic populations, with albumin excretion rates found to be higher in the African Carribbeans compared with Southeast Asians and Europeans (24). In an adolescent population of 647 subjects, Hanevold et al demonstrated that healthy, normotensive black adolescents had an approximate 10% higher albumin excretion rate compared with normotensive white adolescents (25).…”
Section: Discussionmentioning
confidence: 99%